Role of Gender Equity in Sustainable Development - Das, Supriya (Indian Journal of Hill Farming, 2018)
Equity is an essential building block in sustainable development of every sphere of society.Gender analysis is a tool to better understand the realities of the women and men, girls andboys whose lives are impacted by planned development activities. Sustainabledevelopment requires the full and equal participation of women at all levels alongsidemen. It is clearly inappropriate to try and address problems, to identify strategies, or toimplement the programmes, if only half of the population (men/women) concerned isinvolved in the process. Partnerships and equality between men and women are the basisof strong families and viable societies in a rapidly changing world. Women have beenconsistently excluded from decision-making across history and societies; which resultedimbalance, marginalization, suffering and conflicts. Creating greater gender equity willcontribute to building peaceful, democratic and prosperous societies. Even in sustainabledevelopment of agriculture, role of women is of paramount importance and there is urgentneed to devise women specific technologies for better participation and involvement ofwomen in decision making.